2020
DOI: 10.1002/psp.2353
|View full text |Cite
|
Sign up to set email alerts
|

The influence of job accessibility on local residential segregation of ethnic minorities: A study of Hong Kong

Abstract: Previous research has shown that spatial mismatch between residential location and employment opportunities acts as a key influencing factor in employment outcomes for ethnic minorities living in segregated neighbourhoods. However, the effect of job accessibility on residential choice and segregation of ethnic minorities and its relevance to spatial mismatch across different minority groups has not been fully captured, especially in high-density, transit-oriented cities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Research in Tian Shui Wai (an archetypical improvised suburban district in Hong Kong) has further suggested that spatial mismatch, in terms of commute times, costs and limited choices of transport modes, significantly hinders people's access to employment (Lau, 2010). Tao and colleagues also indicate that low-income minority groups are more likely to concentrate in peripheral areas with grave job inaccessibility, compared with other groups (Tao et al, 2020). In summary, previous research has shown that the mismatch between the concentration of population and the geographic distribution of employment opportunities has led to serious unemployment problems among different disadvantaged groups residing in remote areas of Hong Kong.…”
Section: Spatial Mismatch and Precarious Employment In Hong Kongmentioning
confidence: 97%
“…Research in Tian Shui Wai (an archetypical improvised suburban district in Hong Kong) has further suggested that spatial mismatch, in terms of commute times, costs and limited choices of transport modes, significantly hinders people's access to employment (Lau, 2010). Tao and colleagues also indicate that low-income minority groups are more likely to concentrate in peripheral areas with grave job inaccessibility, compared with other groups (Tao et al, 2020). In summary, previous research has shown that the mismatch between the concentration of population and the geographic distribution of employment opportunities has led to serious unemployment problems among different disadvantaged groups residing in remote areas of Hong Kong.…”
Section: Spatial Mismatch and Precarious Employment In Hong Kongmentioning
confidence: 97%
“…In terms of ethnic segregation, past research suggests that the mechanisms behind ethnic segregation in Hong Kong differ from those in North American and European contexts, due to higher density and a more transit-oriented urban form (Tao et al, 2020) and public housing provision (Hui et al, 2012). In other words, it appears that the forms of socio-spatial segregation that are commonly found in other places also exist in Hong Kong, though the mechanisms behind segregation processes are different.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared with foreign studies, the research on mismatch theory in China is relatively late. The application of mismatch theory mainly focuses on the study of residential problems [13,14], the mismatch of job-housing space and residential-commercial space [15,16], the mismatch of urban human settlements [17], the mismatch of public services [18,19], and the spatial pattern of tourism economic system mismatch [20], etc.…”
Section: Literature Reviewmentioning
confidence: 99%